THE TAWASUL BERBASIS GURU MENURUT MUHAMMAD LUTHFI GHOZALI: PENDEKATAN HERMENEUTIK DAN TEOLOGIS - Muhamad Fatoni; Englia Dwikayusi Anggraini (IAIN PONOROGO, 2026)
This study examines the concept of tawasul through the role of the teacher as presented by Muhammad Luthfi Ghozali in Mencari Jati Diri Volume 1: Tawasul Seeking Allah and the Prophet through the Path of the Teacher, focusing on epistemological, practical, and theological issues arising from positioning the teacher as the dominant spiritual intermediary. Research objectives include hermeneutic explanation of the tawasul concept, identification of main problems such as student dependency and teacher authority ambiguity, and analysis of tensions between the teacher's position and tawhid principles. Qualitative library-based methodology employs Hans-Georg Gadamer's hermeneutics, involving close reading of the primary text, triangulation of secondary Sufism data, and the hermeneutic circle for horizon fusion. Findings reveal tawasul as a valid means of inner transformation, with the teacher serving as a proportional wasilah; problems are addressed via contextual Sufi understanding; theological tensions are clarified to align with absolute dependence on Allah.